Prediction of cardiocerebrovascular and other significant disease from disturbed sleep and work strain - Leineweber, Constanze; Kecklund, Göran; Orth-Gomér, Kristina (Scandinavian Journal of Work, Environment & Health, 2007)
' ' OBJECTIVES ': 'This study aimed at describing women’s sleeping habits over a period of 9 years and at examining sleep disturbances in relation to cardiovascular, cerebrovascular, metabolic and other diseases, employment status, and work strain. ' ' METHODS ': 'Altogether 300 healthy women aged 30 to 65 years, randomly selected from the normal population, completed questionnaires at baseline about their sleep, work strain, and lifestyle and were examined for cardiovascular risk factors. The participants were then followed for 9 years and reexamined. The women who contracted a cardiovascular, cerebrovascular, or metabolic disease (N=27) were compared with those who developed other diseases (N=123) and those who remained healthy (N=140) during the follow-up period. ' ' RESULTS ': 'The women with a cardiovascular, cerebrovascular, or metabolic disease in the follow-up examination had higher cholesterol levels (P<0.001), a more sedentary lifestyle (P<0.01), and more work strain (P=0.02) at baseline than those who remained healthy. They also had more sleep disturbances with a borderline significant difference at baseline (P=0.07). In the follow-up examination both the women with a cardiovascular, cerebrovascular, or metabolic disease and those with other illnesses more frequently reported disturbed sleep than those who remained healthy (P=0.002). Poor sleep predicted the incidence of illness. Work strain was associated with disturbed sleep at baseline (P<0.001) but not at the end of the follow-up. ' ' CONCLUSIONS ': 'General and cardiovascular health are important factors for middle-aged women’s subjectively rated sleep quality, and poor sleep can, to some degree, be an early sign of subclinical cardiocerebrovascular disease. Work strain affects sleep in the acute phase but seems to have no long-term effects on sleep quality.
Keywords: cardiocerebrovascular disease; coronary disease; disturbed sleep; job strain; prediction; sick leave; woman; work strain